THE APPLICATION OF MODERN TECHNOLOGICAL MODES FOR THE MAINTENANCE OF BREAST FEEDING - O. L. Lukoyanova; T.E. Borovik; I. A. Belyaeva; G. V. Yatsyk (Вопросы современной педиатрии)
The maintenance of breast feeding when it is complicated due to mother and/or child health state is an important and difficult challenge. The application of bottles and nipples which contribute to imitation of the child’s suction process of mother’s breast is urgent to the lactation maintenance. The aim of the study was to perform comparative evaluation of different series bottles with nipples usage for artificial feeding of infants of the first months of life. The received results showed that the majority of children were more willingly to be fed with «Natural» series nipples, continuing to be breast-fed.